2020
DOI: 10.3390/polym12020349
|View full text |Cite
|
Sign up to set email alerts
|

High-Capacity, Fast-Response, and Photocapacitor-Based Terpolymer Phosphor Composite

Abstract: This paper describes a new class of light transducer-based poly (vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE)) terpolymer doped with 50% wt. phosphor particles that enables to efficiently transform light energy into an electrical signal. Broadband dielectric characterization together with experimental results on photo-electric conversion demonstrated high capacitance variation of the proposed composite under light exposure, confirming promising potential of our sensor device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Such a phenomenon has been useful in developing photosensitive and photostrictive actuators 18 . There are also reports on visible light photo capacitors for the charge storage using dye-sensitized semiconducting nanoparticles 19 , phosphors 20 , photosensitive conjugated polymers 21 , and through a hybrid plasmonic effect of Ag nanowires 22 . However, hybrid perovskites 23 , 24 attracted considerable attention because of their exceptional optoelectronic properties such as excellent light absorption, long carrier lifetime, low trap density, giant optical anisotropy 25 , and high carrier mobility 26 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a phenomenon has been useful in developing photosensitive and photostrictive actuators 18 . There are also reports on visible light photo capacitors for the charge storage using dye-sensitized semiconducting nanoparticles 19 , phosphors 20 , photosensitive conjugated polymers 21 , and through a hybrid plasmonic effect of Ag nanowires 22 . However, hybrid perovskites 23 , 24 attracted considerable attention because of their exceptional optoelectronic properties such as excellent light absorption, long carrier lifetime, low trap density, giant optical anisotropy 25 , and high carrier mobility 26 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a relaxor poly(vinylidene fluoride-trifluoroethylene-1,1-chlorofluoroethylene/chlorotrifluoroethylene) terpolymer (abbreviated as P(VDF-TrFE-CFE/CTFE)), when being doped with a plasticizer, shows an excellent electromechanical response [ 15 ]. Commonly used as actuators [ 16 , 17 , 18 ] or sensors [ 19 , 20 , 21 , 22 , 23 , 24 ], the terpolymer also exhibit particularly impressive abilities when it comes to electroadhesion. For instance, it has been demonstrated that fluorinated terpolymer can hold a frictional shear stress of 21 N/cm 2 when subjected to an electrical field of 24 V/µm [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Capacitors with optically-variable properties attract research interest due to their potential application in a variety of electronics devices. For example, the search for sustainable electric power supply is currently concentrated on photo-powered energy sources, and photocapacitors are an innovation in this field with promising applications in integrated devices such as medical sensors [1,2] and next generation solar cells [3][4][5][6]. Furthermore, the property of light-dependent capacitance of photovaractors is useful for optical control or modulation of microwave signals [7,8].…”
Section: Introductionmentioning
confidence: 99%